2019
DOI: 10.1002/cctc.201801908
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Zn‐Doped CoO Nanoflowers for Electrocatalytic Oxygen Evolution Reaction

Abstract: Hierarchical Zn-doped CoO nanoflowers have been prepared using their hydroxides as precursors. The nanoflowers are assembled by dozens of 2D nanoplates. Each nanoplate is formed by numerous Zn-doped CoO nanoparticles. Zn-doped CoO catalyst is highly efficient for electrocatalytic water oxidation with a low overpotential (η = 293 mV at j = 10 mA cm À 2 ) and long-term stability, which is comparable to the commercial RuO 2 catalysts in alkaline media. The 3D hierarchical structure provides abundant surface catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…Among doped series, composition with Ni 0.3 Co 0.7 O catalyst displays highest OER activity with e g value of ~1.3. Huo et al reported improved OER performance of CoO nanoflowers by doping with Zn 106. DFT study confirmed that OER active sites were increased by Zn doping, and high surface area of nanoflowers was another contributor to the improved catalytic activity.…”
mentioning
confidence: 96%
“…Among doped series, composition with Ni 0.3 Co 0.7 O catalyst displays highest OER activity with e g value of ~1.3. Huo et al reported improved OER performance of CoO nanoflowers by doping with Zn 106. DFT study confirmed that OER active sites were increased by Zn doping, and high surface area of nanoflowers was another contributor to the improved catalytic activity.…”
mentioning
confidence: 96%
“…However in terms of the less studied CoO x material, the performance is slightly better than CoO nanobers 52 in terms of overpotential at 10 mA cm À2 and comparable to previous reports of CoO nanomaterials which were investigated in a more concentrated alkaline electrolyte of 1 M KOH, compared to 0.1 M used here, which gave values of 400 mV for both nanoparticles 53 and nanoplates. 54 Again the activity of CoO can be improved via doping with a second metal such as Fe 52 and Zn 54 but this was not the goal of the current study.…”
Section: Resultsmentioning
confidence: 92%
“…Compared with CoS x , the binding energy of Co 2P 3/2 orbital of Co 3+ in ZnCoS (779.17 eV) presents a negative shift of 0.26 eV and the Co 3+ /Co 2+ ratio increases to 4.7/1, similar to the reported Zn‐doped cobalt compounds. [ 36 , 37 ] In contrast, by further incorporating Ti element, the Co 2P 3/2 peak (779.31 eV) shifts toward higher binding energy, and the Co 3+ /Co 2+ ratio decreases from 4.7/1 to 3.7/1 due to the electron density shift from Ti to Co center, [ 38 , 39 ] which locates between ZnCoS and CoS x . When increasing the Co/Zn ratio, the binding energy of Co 2P 3/2 (≈779.39 eV) in Ti–ZnCoS HSS‐1 further increases.…”
Section: Resultsmentioning
confidence: 99%